2019
DOI: 10.3390/toxics7010018
|View full text |Cite
|
Sign up to set email alerts
|

Propensity of Tagetes erecta L., a Medicinal Plant Commonly Used in Diabetes Management, to Accumulate Perfluoroalkyl Substances

Abstract: It has been extensively demonstrated that plants accumulate organic substances emanating from various sources, including soil and water. This fact suggests the potentiality of contamination of certain vital bioresources, such as medicinal plants, by persistent contaminants, such as perfluorooctanoic acid (PFOA), perfluorooctane sulfonate (PFOS), and perfluorobutane sulfonate (PFBS). Hence, in this study, the propensity of Tagetes erecta L. (a commonly used medicinal plant) to accumulate PFOA, PFOS, and PFBS wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Figure 6 illustrates the effect of dyebath pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) on K/S values of the dyed fabrics. It is observed that the optimum K/S is obtained at acidic pH of 4.…”
Section: Effect Of Ph In Dyeing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 illustrates the effect of dyebath pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) on K/S values of the dyed fabrics. It is observed that the optimum K/S is obtained at acidic pH of 4.…”
Section: Effect Of Ph In Dyeing Processmentioning
confidence: 99%
“…The main colorant components of marigold flower are carotenoid compounds such as lutein and lutein esters. Lutein (C40H56O2) (Figure 2) is a bright yellow xanthophyll pigment and is very popularly used in medical and food industries [7,8]. A study has shown that lutein is a pigment, which is water soluble and behaves like a dye [9].…”
Section: Introductionmentioning
confidence: 99%
“…Voigt (Benin, Kenya, Togo and Uganda), Ximenia americana L. (Guinea, Kenya, South Africa and Zambia), and Zanthoxylum chalybeum Engl (Kenya, Rwanda, Uganda and Zambia) [11]; and for the management of human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs) in the sub-Saharan region, Ximenia americana has been in use (Zambia, Uganda and Kenya), and Azadirachta indica (Uganda and Kenya) [89][90][91]. Similarly, numerous studies have highlighted the antidiabetic potential of several hundreds of sub-Saharan African medicinal plants [4].…”
Section: Pfass As a Threat To Sub-saharan African Medicinal Plantsmentioning
confidence: 99%
“…These plants are an important mode of combat to serious illnesses and diseases in the world [3]. These crops and their derivatives are used for healing by various populations, and in extreme scenarios, these plants have been chosen as natural alternatives or substitutes to their orthodox counterparts [4]. Reported evidence has indicated that these natural products and their derivatives account for an estimated more than 50% of all the drugs used globally [5].…”
Section: Introductionmentioning
confidence: 99%
“…Plants belonging to this genus have important medicinal value. Several studies have suggested that T. erecta has the potential to treat ailments, such as diabetes mellitus (Mudumbi et al 2019). In particular, the flowers have been used to cure eye diseases, colds, conjunctivitis, coughs, ulcers, bleeding piles, and to purify the blood (Hemali and Sumitra 2014).…”
Section: Introductionmentioning
confidence: 99%